PENGEMBANGAN MEDIA PUZZLE JARING – JARING KUBUS DAN BALOK (JAJAN KUBAL) UNTUK PEMBELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR - Kristiyawan, Firda Agus; Rarasati, Ida Putri; Widiastuti, Sripit (Transpublika Publisher, 2023)
Mathematics plays a crucial role in solving various problems and developing students' competencies in organizing their thoughts and tackling everyday challenges. The purpose of teaching mathematics to students is to equip them with the skills necessary to think carefully, systematically, analytically, critically, logically, and creatively in their daily lives. This research aims to test and evaluate the effectiveness of the nets of cubes and blocks (jajan kubal) puzzle as a learning tool for fifth-grade mathematics at SD Negeri 8 Tambakasri. The research and development process involved assessing the validity of the nets of cubes and blocks puzzle media by subjecting it to evaluation by content experts, media experts, and linguists. The results obtained from the evaluation indicate that the the nets of cubes and blocks puzzle media is highly valid, with material experts scoring it at 74% (qualified as very good), media experts at 87% (qualified as very good), and linguists at 77% (qualified as good). Additionally, the media's readability for students scored 82%, indicating positive outcomes, while the teacher's assessment yielded a result of 88%, indicating a good value from the teacher's perspective. Therefore, the the nets of cubes and blocks puzzle learning media is deemed feasible and can be implemented as a valuable resource for mathematics education in the second semester of grade V at SD Negeri 8 Tambakasri.